Structural change, commodity dependence and middle-income trap: Emerging approaches to a traditional agenda - Isabella, Fernando (PSL Quarterly Review, 2024)
The objective of this paper is to revisit key themes of development literature in the light of novel emerging approaches. Applying complexity economic tools, evidence is presented to argue that, along the development trajectory of countries, a complexity increase, to be sustainable, must go hand in hand with a departure from their productive historical path, in the form of unrelated diversification. Also, it is argued that successful trajectories must avoid the middle-income trap (MIT), which is shown to stem from the interplay of supply and demand factors. Finally, building on balance of payments constrained growth literature, a theoretical model is proposed to explain the high prevalence of MIT situations among commodity-dependent countries. It is suggested that this phenomenon arises from the interaction of commodity price volatility and real exchange rates, which affects the accumulation of sophisticated productive capabilities.